The role and prospects of skin microbiota in dermatosis - Yuanyuan Chen; Zhijian Yao; Zhuren Ruan; Gao Wei; Wenjun Zheng; Xianghui Li (Therapeutic Advances in Infectious Disease)
The skin microbiota is crucial in defending against toxic, solar, and pathogenic assaults, yet it can also precipitate dermatosis when its equilibrium is disrupted. The composition and distribution of various microorganisms within the skin maintain a dynamic balance, modulating the barrier function and the immune system, thereby constituting the skin microbiota. This microbiota not only offers new insights into pathological microbe-host interactions and associated dermatoses but also inspires innovative therapeutic strategies that promise high efficacy and reduced symptomatology. In this review, we synthesize recent advancements in the field of skin microbiota, focusing on its relationship with dermatosis and the application of microbiota-based therapies in skin diseases. Our aim is to scrutinize the current understanding of the skin microbiota’s role, ranging from a protective barrier to a causative agent of dermatosis.